2014
DOI: 10.1093/bja/aet374
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative decrease in plasma sodium concentration after infusion of hypotonic intravenous solutions in neonatal surgery

Abstract: Hypotonic solutions and i.v. free water intake of more than 6.5 ml kg(-1) h(-1) are associated with reductions in postoperative plasma sodium measurements ≥4 mM. In the context of neonatal surgery, close monitoring of plasma sodium is mandatory. Routine use of hypotonic i.v. solutions during neonatal surgery should be questioned as they are likely to reduce plasma sodium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…In a recent study, Edjo Nkilly et al . observed cases with dilutional hyponatremia following the intraoperative use of hypotonic solutions in neonates. They concluded that intraoperative i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Edjo Nkilly et al . observed cases with dilutional hyponatremia following the intraoperative use of hypotonic solutions in neonates. They concluded that intraoperative i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Though Group D4 patients received 90 mmolÁl À1 sodium in the intraoperative fluid as compared to Group D1 and D2 who received 130 mmolÁl À1 sodium, no incidence of postoperative hyponatremia was observed in any of the patients in Group D4. In a recent study, Edjo Nkilly et al (30) observed cases with dilutional hyponatremia following the intraoperative use of hypotonic solutions in neonates. They concluded that intraoperative i.v.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the perioperative setting, children are at risk of hyponatremia and cerebral edema, as they have a smaller intracranial volume, and the increasing levels of the antidiuretic hormone (ADH) when the body is subject to stress inhibit the excretion of free water . Neonates also have a higher risk of hyponatremia if hypotonic solutions for infusion are used intraoperatively . As compared to normal saline, hyperchloremic acidosis occur more rarely if solutions for infusion with a lower chloride concentration and acetate as bicarbonate precursor are used .…”
Section: Which Solution For Infusion Should Be Used For the Intraopermentioning
confidence: 99%
“…A change in sodium concentration of greater than 4 mM was statistically associated with increases in intraoperative free water volumes. 27 Lonnqvist suggests that isotonic solutions for maintenance in neonates should be considered. 28 A novel isotonic balanced salt solution BS-G1 has been used recently in 66 neonates in a multicentre trial from Germany.…”
Section: Should Maintenance Fluids Be Hypotonic or Isotonic?mentioning
confidence: 99%